PENILAIAN POSTUR TUBUH PEKERJA HPES PLATING DI PT. ABC MENGGUNAKAN METODE OWAS - Annisa Purbasari; Radhiyatan Mardhiyah (Universitas Riau Kepulauan, 2022)
PT. ABC is a company engaged in the production and management of metal and plastic electron components, namely Presicion Metal Stamping and Forming, Precision Cold Forged Treatment and Surface Treatment. One of the departments in this company is the HPES Plating department. In production line activities at HPES Plating, there is work that is predominantly done in the work posture, namely standing, sitting, and bending as well as manual lifting handling activities. This study aims to assess the body posture scores of workers in the HPES Plating department of PT. ABC which has the potential for musculoskeletal disorders using the OWAS method. The results of the posture assessment at the time of incoming product inspection activities were 1, receiving system activities were 1, product transfers were 1, product lifting was 3, jigging activities were 1, product preparation was 2, loading activities were 1, VMI inspections were 1, product packing was 3, OQA inspections were 1, and shipment activities were 2. So that immediate improvements are needed for the work posture of product lifting, product preparation, product packing and shipment.